A motion analysis in the volleyball spike - part 1: Three-dimensional kinematics and performance - Serrien, B.; Ooijen, J.; Goossens, M.; Baeyens, J.-P. (International Journal of Human Movement and Sports Sciences, 2016)
In this study, three-dimensional kinematics and performance were analyzed for male and female top level and junior elite volleyball players in a spike, which is an essential offensive volleyball action. Top level players had higher impact speeds and jumping height than junior elite players for both genders and the male players had higher impact speeds and jumping height than the female players for both levels of expertise. For the analysis of the three-dimensional kinematics of the pelvis, trunk, shoulder and elbow angles and angular velocities, Statistical Parametric Mapping was used. No differences were observed for the orientation angles of pelvis and trunk, indicating a set of invariant kinematics. The pelvis and trunk angular velocities on the other hand did show many interesting differences throughout the approach, cocking and acceleration phase of the spike. The shoulder and elbow angles and angular velocities also illustrated the different strategies used for generating high impact speeds. An important conclusion was that interaction effects between gender and level of expertise were mostly observed in variables from the shoulder and elbow, whereas pelvis and trunk velocities only presented significant main effects. These differences suggest how the motion pattern of the young elite athletes will change over the following years when they gradually make the change towards the highest competitive levels.